Study of lactic acid fermentation for the extraction of chitin from shellfish waste - Marcia, E; Malespín, J; Sánchez, M; Benavente, M (Nexo Revista Científica, 2011)
The extraction of chitin from crustacean waste involved the deproteinisation and demineralisation of crustacean shells using lactic acid fermentation with whey and sucrose as culture medium and carbon source, respectively. The fermentation process was carried out in a vertical Pyrex reactor of 4 L by 2 and 3 weeks at room temperature. The results showed that a good deproteinisation and demineralisation was obtained; however, the product still contained traces of proteins and pigments. Therefore, it was necessary to apply a chemical process with sodium hydroxide and sodium hypochlorite, to completely remove the proteins and pigments from the structure of crustacean shell. A recovery of 85 % was obtained. The comparison of FT-IR spectra of chitin produced and a sample of commercial chitin showed a correlation rate of 93-95 %, indicating that chitin produced using the combined method has a high degree of purity. Keywords: Chitin; Shrimp shell; Sucrose; Vertical reactor; Whey DOI: http://dx.doi.org/10.5377/nexo.v24i1.592 Nexo, Vol. 24, No. 1, pp. 33-42, 2011